Pengembangan Bahan Ajar Kompetensi Menulis Sandhangan Mandaswara Bagi Kelas X SMK N 6 Semarang - Burhani, Dewi Amalia; Mujimin, Mujimin (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
Javanese script learning often has gaps between targets and outcomes, especially in the writing competence of Sandhangan mandaswara. The mistakes lies in writing words, sentences, and paragraphs. The purpose of this study is to describe the needs of materials, arrange the design of teaching materials, and describe the results of expert tests. The data sources are students grade X of SMK N 6 Semarang, teachers, and lecturers. Data collection techniques were carried out using observation, interviews, questionnaires, and expert test assessment sheets. The results was the needed of additional books which are interesting and contains complete material to guide students in learning sandhangan mandaswara. Prototype design of instructional materials was developed using the structure of instructional materials that have been restructured into a structure of teaching materials. The structure of these basic teaching materials includes; 1) learning objectives; 2) subject matter; 3) assessment. The results of the validation assessment of the material experts and users are divided into 3 aspects of the assessment. The relevance aspect gained an average value of 91.67% (very feasible), the consistency aspect gained an average of 86.11% (very feasible), the adequacy aspect gained an average value of 85.83% (very feasible). Conclusions from these aspects of the assessment obtained an average value of 87.25% with a very decent category. Then according to the 3 validators, the developed teaching material is very suitable for use in learning although it still needs revision to improve the quality of the teaching material.